2011
DOI: 10.1179/2045772311y.0000000016
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of rehabilitation outcomes following vascular-related and traumatic spinal cord injury

Abstract: VR-SCI leads to significant disability and is associated with common secondary SCI complications as well as medical co-morbidities. This study notes differing demographic and injury characteristics between VR-SCI and T-SCI groups. However, when matched for these differences, rehabilitation functional outcomes were not significantly different between the two groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 17 publications
0
14
1
Order By: Relevance
“…Despite the differences in the systems of care, our patient population reached and even exceeded their potential motor FIM change by specific injury level according to the expected functional scores published by the Paralyzed Veterans of America. 26 As a result of the long LOS in our data, however, the motor FIM efficiency in our study was quite low (0.43 for all patients) compared with other recent SCI studies that reported a motor FIM efficiency of 0.7 ( n = 30, rehabilitation LOS = 36 days) 27 and 0.95 ( n = 775, rehabilitation LOS = 51 days). 28 …”
Section: Discussioncontrasting
confidence: 63%
“…Despite the differences in the systems of care, our patient population reached and even exceeded their potential motor FIM change by specific injury level according to the expected functional scores published by the Paralyzed Veterans of America. 26 As a result of the long LOS in our data, however, the motor FIM efficiency in our study was quite low (0.43 for all patients) compared with other recent SCI studies that reported a motor FIM efficiency of 0.7 ( n = 30, rehabilitation LOS = 36 days) 27 and 0.95 ( n = 775, rehabilitation LOS = 51 days). 28 …”
Section: Discussioncontrasting
confidence: 63%
“…In one study, Jellema et al 22 found 11 cases of SDAVF out of 1429 patients admitted to SCI ward of a rehabilitation center in 24 years. In another study examining the rehabilitation outcome of vascular-related SCI, 23 5 (17%) patients out of 30 patients had SDAVF in 10 years. It seems that the majority of patients with SDAVF do not require inpatient rehabilitation treatment.…”
Section: Discussionmentioning
confidence: 98%
“…In the present study neurogenic bladder patterns showed no co-relation with demographic parameters like age, length of stay in rehabilitation and duration of neurological insult like some earlier studies. [ 8 9 10 ]…”
Section: Discussionmentioning
confidence: 99%